OPTIMIZATION OF THE MARKETING CHAIN OF TRADITIONAL PRODUCTS: A CASE STUDY OF SUPUTRA HERBAL INCENSE IN ABIANSEMAL DISTRICT - Frumensius Dakosta Joro; Nyoman Yudiarini; Luh Putu Kirana Pratiwi (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2025)
Dupa Herbal Suputra, a micro, small, and medium enterprise (MSME) located in Angantaka Village, Abiansemal District, Badung Regency, has great potential in developing natural and spiritually significant herbal incense products. This study aims to analyze the marketing channels and calculate the marketing margins of the herbal incense products. The research used a combination of qualitative and quantitative methods. The study was conducted at Dupa Herbal Suputra MSME in Angantaka Village, Abiansemal District, Badung Regency, over a period of two months, from November to December. Data collection instruments included interviews and recordkeeping. The results showed that there are three marketing channel patterns: (1) a one-level channel (producer–consumer), (2) a two-level channel (producer–retailer–consumer), and (3) a three-level channel (producer–collector–retailer–consumer). The marketing margin for Dupa Herbal Suputra was zero in the first channel due to direct transactions. The second channel yielded a margin of IDR 3,000, while the third channel provided a margin of IDR 5,000. This study recommends enhancing direct marketing through digital platforms to improve efficiency and producer margins. In addition, training in business management and market access is important to improve the competitiveness of local MSMEs.